Пошаговое объяснение:
а)
4х-х=8+1.
3х=9.
х=3.
б)
1/6х-х=-1,5.
-5/6х=-3/2.
х=9/5=1 4/5.
в)
1/х=-2+1/6=-1 5/6=- 11/6.
х=-6/11.
4х-8=х+1
4х-х=8+1
3х=9
х=3
1:6х+1.5=х
1:6х+3:2=х домножим на 6
х+9=6х
х=9:5=1.8
1:х+2=1:6
1:х=1:6-2
1:х=-11:6
х=-6:11
Пошаговое объяснение:
а)
4х-х=8+1.
3х=9.
х=3.
б)
1/6х-х=-1,5.
-5/6х=-3/2.
х=9/5=1 4/5.
в)
1/х=-2+1/6=-1 5/6=- 11/6.
х=-6/11.
Пошаговое объяснение:
4х-8=х+1
4х-х=8+1
3х=9
х=3
1:6х+1.5=х
1:6х+3:2=х домножим на 6
х+9=6х
х=9:5=1.8
1:х+2=1:6
1:х=1:6-2
1:х=-11:6
х=-6:11